Analisis Komparatif Strategi Pembelajaran Inovatif Terhadap Pengembangan Higher Order Thinking Skill (Hots) Pada Siswa Sekolah Dasar - Made Sri Astika Dewi; Adistia Rahmadani; Amanda Safitri; Azka Aflahiyah; Ni Putu Ayu Intan Pratiwi; Halvi Sukmawati; I Ketut Restu Adi Saputra (Lembaga Pengembangan Kinerja Dosen, 2026)
Developing Higher Order Thinking Skills (HOTS) is essential for 21st-century primary education. This research aims to analyze and compare the effectiveness of various innovative learning strategies in enhancing students' HOTS using a Systematic Literature Review (SLR) of 28 indexed articles (2022–2026). The models examined include Problem-Based Learning (PBL), Project-Based Learning (PjBL), Discovery Learning, Guided Inquiry, and the STEM/STEAM approach. The analysis indicates that all models significantly contribute to improving students' critical thinking, creativity, and problem-solving skills. Specifically, PBL excels in contextual analysis; PjBL effectively fosters collaboration and creativity; Discovery Learning builds conceptual autonomy; Guided Inquiry excels in scientific investigation; and STEM/STEAM facilitates interdisciplinary integration. The study concludes that student-centered learning is the key to HOTS success. Consequently, teachers must demonstrate flexibility by integrating varied learning models according to material characteristics and student needs to support the implementation of the Merdeka Curriculum